2019
DOI: 10.1016/j.fuel.2018.09.092
|View full text |Cite
|
Sign up to set email alerts
|

Steam reforming of shale gas with nickel and calcium looping

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs (CC BY-NC-ND) licence. This licence only allows you to download this work and share it with others as long as you credit the authors, but you can't change the article in any way or use it commercially. More information and the full terms of the licence here: https://creativecommons.org/licenses/ TakedownIf you consider content in White Rose Research Online to be in breach of UK law, please notify us by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 63 publications
(94 reference statements)
1
4
0
1
Order By: Relevance
“…The result depicts a good agreement with the results obtained from CEA. Similar thermodynamic studies were also conducted using several feedstocks including shale gas [4,10], hydroxyacetone [18], palm empty fruit bunch and pine pyrolysis oils [19], and urea [20]. There results showed same trend to those of this study with regards to H 2 yield and purity.…”
Section: Effect Of Temperature On Hydrogen Yield and Puritysupporting
confidence: 80%
See 3 more Smart Citations
“…The result depicts a good agreement with the results obtained from CEA. Similar thermodynamic studies were also conducted using several feedstocks including shale gas [4,10], hydroxyacetone [18], palm empty fruit bunch and pine pyrolysis oils [19], and urea [20]. There results showed same trend to those of this study with regards to H 2 yield and purity.…”
Section: Effect Of Temperature On Hydrogen Yield and Puritysupporting
confidence: 80%
“…Le Chatelier"s principle governs the behaviour of H 2 yield and purity whereby an increase in the water reactant concentration in the system shift the equilibrium towards higher water conversion, thus causing higher H 2 yield and purity (Figure 1). The disadvantage of operating at high S:C ratio is that higher reactor volume will be needed, furthermore, there will be high cost for raising steam [4,10]. Additionally, operating at higher S:C ratio is one of the reasons behind catalyst deactivation owing to pore blockage [4,10,[21][22][23].…”
Section: Effect Of Steam To Carbon Ratio On Hydrogen Yield and Puritymentioning
confidence: 99%
See 2 more Smart Citations
“…Kathe et al investigated the thermodynamic limitations and energy consumption of the natural gas CLR hydrogen generation process using an iron-based oxygen carrier (OC) [18]. Adiya et al investigated using NiO on Al 2 O 3 and NiO on CaO/Al 2 O 3 as catalysts and OC in a packed bed reactor for shale gas chemical looping steam reforming for hydrogen production, which showed a high fuel conversion and yield under operating temperatures of 700 and 750 • C [19,20]. Techno-economics analysis of three hydrogen production processes was investigated by Chisalita and Cormos [21], which concluded that efficient hydrogen production via chemical looping is the most efficient with low maintenance and operating costs.…”
Section: Introductionmentioning
confidence: 99%